Systematic Literature Review of the Concept and Practice of Sharia Leasing: Theoretical and Application Perspectives - Moh. Nasrul Muslim; Taufiqur Rahman (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
The development of Islamic economy and finance at the global level has shown significant growth over the past decade. One important instrument in the development of Islamic financial sectors is sharia-based leasing or operating lease, known in Islamic jurisprudence (fiqh muamalah) as ijarah . This concept not only aims to meet the need for capital goods—both productive and consumptive—but also emphasizes values such as justice, transparency, and compliance with Islamic principles. In practice, sharia leasing differs fundamentally from conventional schemes, especially in terms of cost structure and time conditions. Unlike conventional leasing, which typically uses an interest-based system without full transparency to consumers, all cost components in sharia leasing must be clearly explained to the lessee. Furthermore, one popular form of ijarah in a business context is Ijarah Muntahiyah Bitamlik (IMBT) , a lease contract that ends with the transfer of asset ownership to the lessee, either through a gift or a separate sales agreement. According to data from the Islamic Financial Services Board (IFSB, 2023), the global Islamic financial sector reached more than USD 2 trillion by 2023, with non-banking instruments such as sharia leasing, sukuk, and takaful showing increasing participation. In Indonesia, despite relatively rapid development in the Islamic financial industry, financing through Islamic leasing companies remains limited. As of 2022, the number of full-fledged Islamic multifinance institutions and Sharia Business Units (UUS) offering sharia leasing services was still suboptimal. One of the main challenges in developing sharia leasing is the lack of public awareness regarding its benefits and mechanisms. Additionally, limitations in regulation, low institutional capacity in designing competitive products, and insufficient human resource readiness are obstacles to the widespread implementation of this concept. From a theoretical perspective, many studies have explored sharia leasing from various angles, including fiqh, contract law, and institutional implementation. However, comprehensive and synthetic reviews of these literatures remain limited. Therefore, the systematic literature review (SLR) method is relevant to identify, evaluate, and synthesize findings from previous studies. Through SLR, the author mapped the conceptual and practical development of sharia leasing and identified research gaps that require further investigation. This approach provides a systematic and objective framework to ensure that the analysis is evidence-based and supported by valid references.